“HLA-C: evolution, epigenetics, and pathological implications in the major histocompatibility complex” - Velastegui, Erick; Vera, Edwin; Vanden Berghe, Wim; Muñoz, Mindy S.; Orellana-Manzano, Andrea (Frontiers in Genetics, 2023)
HLA-C, a gene located within the major histocompatibility complex, has emerged as a prominent target in biomedical research due to its involvement in various diseases, including cancer and autoimmune disorders. Despite the fact that its recent addition to the MHC, the interaction between HLA-C and KIR is crucial for immune responses, particularly in viral infections. This review provides an overview of the structure, origin, function, and pathological implications of HLA-C in the major histocompatibility complex. We systematically reviewed original publications from Pubmed, ScienceDirect, Scopus, and Google Scholar in the last decade. Our findings reveal that genetic variations in HLA-C can determine susceptibility or resistance to certain diseases. However, the first four exons of HLA-C are particularly susceptible to epigenetic modifications, which can lead to gene silencing and alterations in immune function. These alterations can manifest in diseases such as alopecia areata and psoriasis and can also impact susceptibility to cancer and the effectiveness of cancer treatments. By comprehending the intricate interplay between genetic and epigenetic factors that regulate HLA-C expression, researchers may develop novel strategies for preventing and treating diseases associated with HLA-C dysregulation.